Unpacking the Black Box: Demystifying Ecological Models Through Interactive Workshops and Hands-On Learning - Herman, Brook D.; McKay, S. Kyle; Altman, Safra; Richards, Nathan S.; Reif, Molly; Piercy, Candice D.; Swannack, Todd M. (Frontiers in Environmental Science, 2019)
Environmental management decisions increasingly rely on ecological models to forecast outcomes of management actions. Models are becoming increasingly complex through the integration of processes from multiple disciplines (e.g., linking engineering and ecological models). These models are often viewed as mysterious, baffling black boxes, which can lead to mistrust, misinterpretation and/or misapplication of model results. Numerical models have historically been developed without decision makers, coordinating partners, or stakeholders playing active roles in model development, which further complicates communication. Ultimately, mistrust of models and associated outputs can lead to poor decision-making, increase the risk of ineffective decisions, and lead to litigation over decisions. Improved ecological model development practices are needed to increase transparency, include stakeholders and decision makers throughout the entire modeling process from conceptualization through application, and overcome common communication barriers. Building from participatory modeling and prototyping methods, we have developed a workshop approach for applied ecosystem modeling problems that cultivates a foundational understanding of ecological models through hands-on, interactive model development. In this workshop environment, interdisciplinary and interagency working groups co-develop models in real-time which demystifies technical issues and educates participants on the modeling process. The purpose of this paper is to synthesize a repeatable mediated modeling workshop and identify its utility in overcoming major communication challenges of integrated modeling for complex environmental problems. The workshop approach informs modeling teams of the complexity facing decision-makers, creates a sense of model ownership by participants, builds trust among partners, and ultimately increases “buy-in” of the eventual decision.